2021
DOI: 10.1016/j.ejca.2020.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Completion of radical hysterectomy does not improve survival of patients with cervical cancer and intraoperatively detected lymph node involvement: ABRAX international retrospective cohort study

Abstract: Background: The management of cervical cancer patients with intraoperative detection of lymph node involvement remains controversial. Since all these patients are referred for (chemo)radiation after the surgery, the key decision is whether radical hysterectomy should be completed as originally planned, taking into account an additional morbidity associated with extensive surgical dissection prior to adjuvant treatment. The ABRAX study investigated whether completing a radical uterine procedure is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Other opinions included the continuation of laparoscopic radical hysterectomy (29%), discontinuation of radical hysterectomy without paraaortic lymph node staging (24%) and conversion to open radical hysterectomy (9%). The ABRAX study was introduced by Dr. Jae Man Bae which demonstrated similar survival outcomes between those who completed radical hysterectomy and those who abandoned radical hysterectomy after finding pelvic lymph node metastasis intraoperatively [ 27 ].…”
Section: Tumor Boardmentioning
confidence: 99%
“…Other opinions included the continuation of laparoscopic radical hysterectomy (29%), discontinuation of radical hysterectomy without paraaortic lymph node staging (24%) and conversion to open radical hysterectomy (9%). The ABRAX study was introduced by Dr. Jae Man Bae which demonstrated similar survival outcomes between those who completed radical hysterectomy and those who abandoned radical hysterectomy after finding pelvic lymph node metastasis intraoperatively [ 27 ].…”
Section: Tumor Boardmentioning
confidence: 99%
“…In case the metastatic lymph node is detected intra-operatively (and possibly confirmed with a staging lymphadenectomy), both the literature evidence and the international guidelines recommend against the continuation of radical surgery in favor of definitive chemo-radiotherapy [ 5 , 6 ]. On the other hand, if the lymph node metastasis is diagnosed after radical hysterectomy and lymphadenectomy, adjuvant chemoradiation is indicated [ 3 , 5 ].…”
mentioning
confidence: 99%
“…In early-stage cervical cancer, the prediction of the positive lymph node may allow avoiding any lymph nodal dissection, including SLN mapping, with the subsequent risk of performing radical surgery in lymph nodes positive patients [6] . Few studies have already shown that for selected very low-risk patients, the probability of metastasis in SLN is negligible and any kind of lymph node dissection could be avoided [15] , [16] : radiomics models may broaden the spectrum of patients in whom lymphadenectomy can be spared including also higher risk patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recently published ABRAX (ABandoning RAd hyst in cerviX cancer) study has not shown any survival benefit resulting from a completion of radical hysterectomy in patients with common cervical cancer types, in whom positive pelvic lymph nodes were diagnosed intraoperatively. 7 Taking into account the fact that neuroendocrine carcinoma is a very rare disease, it is not realistic to conduct prospective trials and come up with level I evidence on the significance of parametrectomy and systematic pelvic lymphadenectomy. Avoiding parametrectomy and limiting lymph node staging to sentinel lymph node biopsy…”
mentioning
confidence: 99%